Hypoglycemic encephalopathy caused by insulinoma: A case report (Indian Journal of Case Reports, 2021)
Hypoglycemic encephalopathy is a critical condition associated with a poor prognosis. Tumor-induced hypoglycemia is a rare clinical condition of hypoglycemia that occurs when a pancreatic islet beta-cell tumor insulinoma produces excessive insulin. We present the case of a non-diabetic 62-year-old woman with a 15-year history of recurrent fasting hypoglycemia, whose symptoms of weakness and giddiness would develop in the early mornings, prompting her to request sweetened tea and glucose cookies, after which her symptoms would improve. Investigations showed raised levels of insulin, C-peptide, pro-insulin, as well as a decreased value of beta-hydroxybutyrate and a negative screen for urine sulfonylureas. Computed tomography abdomen revealed a focal lesion in the body of the pancreas suggestive of insulinoma. Based on these investigations, a diagnosis of endogenous hyperinsulinism was made. This case emphasizes the importance of thorough history taking, attention, and observation in making a new diagnosis that has the potential to alter a patient’s health care and alleviate clinical outcomes, where the patient ignored the symptoms for nearly 15 years, leading to the development of hypoglycemic encephalopathy.